Disentangling the Incentive and Entrenchment Effects of Large Shareholdings - Claessens, Stijn; Djankov, Simeon; Fan, Joseph P. H.; Lang, Larry H. P. (Journal of Finance, 2002)
ABSTRACT This article disentangles the incentive and entrenchment effects of large ownership. Using data for 1,301 publicly traded corporations in eight East Asian economies, we find that firm value increases with the cash‐flow ownership of the largest shareholder, consistent with a positive incentive effect. But firm value falls when the control rights of the largest shareholder exceed its cash‐flow ownership, consistent with an entrenchment effect. Given that concentrated corporate ownership is predominant in most countries, these findings have relevance for corporate governance across the world.